Analysis of the Implementation of Tax Planning in Efficient Corporate Income Tax at PT. Campina Ice Cream Industry, Tbk - Siti Salama Amar; Devi Lestari Pramita Putri (Journal of Economics, Business, and Government Challenges, 2022)
The purpose of this study was to analyze the application of tax planning in corporate income tax efficiency at PT. Campina Ice Cream Industry, Tbk. in accordance with the general provisions of applicable taxation.PThis research is motivated by the development of the business world which is influenced by the provisions of tax laws and the development of companies that want their business to generate maximum corporate profits, so that the company will receive capital to improve the company's operational performance.Types of researchThis is a quantitative descriptive study. The technique used in the data collection procedure is documentation, the data is obtained from the official website of the Indonesia Stock Exchange (IDX) 1 Profit and Loss Report and Profit and Loss Report after Fiscal Reconciliation from PT Campina Ice Cream Industry, Tbk. by analyzing the data referring to the theoretical basis, reviewing the processed data and its application based on the General Provisions of Taxation for the efficiency of Corporate Income Tax (PPh).Research resultsthis can be a guidance for companies in implementing Corporate Income Tax Calculation with cost efficiency based on legality, and consistent theories so that research shows that the implementation of tax planning by PT. Campina Ice Cream Industry, Tbk. will prove to be able to streamline the tax burden. The results of the tax planning conducted by PT. Campina Ice Cream Industry, Tbk. is the burden of corporate income tax which also decreases, this cannot be said to be effective because the taxable profit of the company decreases. It is said to be effective efficient if the company's profit has increased. Tax planning can be used as a means of tax management that can support the efficiency of the company's tax burden.